Depopulation of the Northern Border of Mesoamerica during the Early Postclassic: Evidence from the Reappraisal of Archaeomagnetic Data - Alejandra García Pimentel; Avto Goguitchaichvili; Carlos Torreblanca; Vadim Kravchinsky; Miguel Cervantes; Rafael García; Rubén Cejudo; Francisco Bautista; Juan Morales (Land, 2022)
The Mesoamerican Postclassic and Epiclassic were periods of drastic change and transformation related to social, political and economic aspects as well as settlement patterns. Mexico’s northern boundary expansion, rise, and subsequent demise is a matter of debate which remains essentially unsolved. Possible causes include climatic changes, landscape degradation or prolonged bellicose relations with nomadic groups. Still, no consensus exists on why such apparent instability and decline occurred at major archaeological settlements on the northern Mesoamerican border, also known as the septentrional frontier. The scarcity of absolute chronological constraints is definitively a handicap that impedes the assessment of northern Mesoamerica’s development from its apogee to its decline. The archaeomagnetic method has been used during the last decades to analyze burned archaeological artifacts belonging to Mesoamerica’s north and central-west frontiers, including different Mexican states. Namely, high-resolution studies were carried out at Aguascalientes (El Ocote), Guanajuato (El Cóporo, Lo de Juárez and Plazuelas), Jalisco (Cerro de Los Agaves, La Palma and El Palacio de Ocomo) and Zacatecas (La Quemada). It was successfully proved that archaeomagnetic dating might greatly contribute to refining the chronology and development of major pre-Hispanic settlements. These studies were based on available geomagnetic curves at the time of publication. However, global geomagnetic models have experienced substantial improvement with the development of local/regional reference archaeomagnetic curves during the last few years. Hence, the need arises for a critical reassessment of reported age intervals and corresponding chronological contexts. Updated archaeomagnetic ages are recalculated considering the geomagnetic models SHA.DIF.14K and SHAWQ.2K as well as the two regional paleosecular variation curves for Mesoamerica. A bootstrap resampling method is used to obtain an optimal age range for each studied structure. These new absolute chronologies indicate that the last fire exposure of the vast majority of the analyzed artifacts unequivocally corresponds to the Mesoamerican early Postclassic related to the depopulation stage apparently caused by environmental changes.